If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(10) = ln(x + -1) + -1ln(18) Reorder the terms for easier multiplication: 10nL = ln(x + -1) + -1ln(18) Reorder the terms: 10nL = ln(-1 + x) + -1ln(18) 10nL = (-1 * ln + x * ln) + -1ln(18) 10nL = (-1ln + lnx) + -1ln(18) Reorder the terms for easier multiplication: 10nL = -1ln + lnx + -1 * 18ln Multiply -1 * 18 10nL = -1ln + lnx + -18ln Reorder the terms: 10nL = -1ln + -18ln + lnx Combine like terms: -1ln + -18ln = -19ln 10nL = -19ln + lnx Solving 10nL = -19ln + lnx Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '19ln' to each side of the equation. 19ln + 10nL = -19ln + 19ln + lnx Combine like terms: -19ln + 19ln = 0 19ln + 10nL = 0 + lnx 19ln + 10nL = lnx Add '-1lnx' to each side of the equation. 19ln + -1lnx + 10nL = lnx + -1lnx Combine like terms: lnx + -1lnx = 0 19ln + -1lnx + 10nL = 0 Factor out the Greatest Common Factor (GCF), 'n'. n(19l + -1lx + 10L) = 0Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(19l + -1lx + 10L)' equal to zero and attempt to solve: Simplifying 19l + -1lx + 10L = 0 Reorder the terms: 10L + 19l + -1lx = 0 Solving 10L + 19l + -1lx = 0 Move all terms containing n to the left, all other terms to the right. Add '-10L' to each side of the equation. 10L + 19l + -10L + -1lx = 0 + -10L Reorder the terms: 10L + -10L + 19l + -1lx = 0 + -10L Combine like terms: 10L + -10L = 0 0 + 19l + -1lx = 0 + -10L 19l + -1lx = 0 + -10L Remove the zero: 19l + -1lx = -10L Add '-19l' to each side of the equation. 19l + -19l + -1lx = -10L + -19l Combine like terms: 19l + -19l = 0 0 + -1lx = -10L + -19l -1lx = -10L + -19l Add 'lx' to each side of the equation. -1lx + lx = -10L + -19l + lx Combine like terms: -1lx + lx = 0 0 = -10L + -19l + lx Simplifying 0 = -10L + -19l + lx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
n = {0}
| 2-5(x-6)=x+12-8x | | 4-(x-3)=x+7 | | 8n-11=29 | | 2(90+-1y)+2y=180 | | 0.25x^2-x-2=0 | | 108y^2-3xy-x^2= | | 0=x^2-8x+4 | | 0.5x^2-x-10=0 | | 12c-5+15c+27= | | 8y^2-23y-3=0 | | 96y^2-22xy+x^2= | | Y=x^2-8x+4 | | m(m-2)=24 | | 5(3n+1)=7(6n+9)+2 | | x^2-2x-5=30 | | -22=n-16 | | 0.9x^2+5.4x-4=0 | | z-1=4(7z-4) | | 0=16x^2+8x+1 | | 5v+3=18 | | 3a(3a+2a-7)= | | 220=0,22.x | | w^2+2wj-35j^2= | | 3x^2+15x-3=0 | | 220=1,1.x | | x^2+9x-90= | | -12y-14=142 | | 2x+3x+1=7x-11 | | 5-(4+2x)=2x+8 | | x^2+19x+12=-48 | | -y(5y-3y+2y)= | | 220=2,2.x |